Behavior of meteorological drought indices across spatial and temporal dimensions - Núñez-Magaña, Tania Gudelia; Ruíz-Acosta, Silvia del Carmen; Palomeque-de la Cruz, Miguel Ángel; Galindo- Alcántara, Adalberto (Ecosistemas y Recursos Agropecuarios, 2022)
The phenomenon of meteorological drought has been the object of study due to the environmental disasters it causes, and the estimate of meteorological drought indices (IDs) allows to quantify the damages, thus helping to generate mitigation plans. The objective was to determine the intensity or extensity of the greater application IDs to improve its evaluation. A systematic revision of published works from the last 40 years was carried out, which included an analysis of the behavior of the spatial dimensions, temporals, climate of the system with the results produced by the IDs. The analysis revealed that are intensive. This causes IDs assessments to have spatial influence, observation points, data length, weather, and temporal scale. In addition, the feasibility of the IDs is pointed out for its application, reaching a higher accuracy in the evaluations.